Argama: Generating games from plain English - HAGMAR, MARTIN; KITZING, SARA; MARKAN, STINA; OTTERLIND, OLIVER; ROHDIN, JACOB (My University, 2019)
The purpose of the thesis was to develop a web application for students where they can create a game by writing a game plan in plain English. The goals were to use modern coding practices and principles in the development, and the application should contain similar functionality as GameChangineer while being more userfriendly. GameChangineer was evaluated in order to identify possible improvements in regard to user experience. A controlled natural language was defined in order to interpret game plans. A server was implemented to handle the generation of Processing code that was used to display the game on the web application. The outcome of the project was a web application using mostly modern practices and principles, with a functionality close to the GameChangineer website, but less complex. The final user test showed that the application’s user experience improved compared to GameChangineer.
Keywords: Controlled natural language; Grammatical Framework; Processing; GameChangineer; game generation; user experience